Developing Actinobacterial Endophytes as Biocontrol Products for Fusarium pseudograminearum in Wheat - O’Sullivan, Cathryn A.; Roper, Margaret M.; Myers, Cindy A.; Thatcher, Louise F. (Frontiers in Bioengineering and Biotechnology, 2021)
Crown rot of wheat, caused by Fusarium pseudograminearum, results in millions of dollars of yield losses globally each year. Management strategies to control crown rot are limited and there are concerns about development of fungicide resistance so novel treatment strategies are desirable. A collection of endophytic Actinobacteria was screened for their ability to suppress the growth of F. pseudograminearum and the development of crown rot symptoms in wheat with the aim of identifying candidates that can be developed into biocontrol products. The ability of the Actinobacteria isolates to suppress the growth of three different F. pseudograminearum strains in-vitro was assessed using agar-plate competition assays. Soil-free seedling assays were used to screen for suppression of development of early disease symptoms in the susceptible wheat (Triticum aestivum) cv. Tamaroi. Four of the isolates were tested in a glasshouse pot experiment to assess their ability to decrease disease symptoms and prevent yield losses in wheat cv. Tamaroi grown to maturity in an unsterilized soil. The screening of 53 isolates identified two Streptomyces isolates, MH71 and MH243, with very strong antifungal activity against F. pseudograminearum strains in agar-plate competition and seedling assays. In the glasshouse pot trial, plants treated with seed coatings of either MH71 or MH243 had significantly lower stem browning and 22.5% lower yield losses than control plants infected with F. pseudograminearum. These two cultures show potential for development as biocontrol products because they are easy to culture, grow on relatively inexpensive media, produce highly durable spores and can be delivered to plants as a seed coat.